Implementation of Teaching Religious Character Through School Culture to Grade 3 Students at Muhammadiyah Elementary School 2 Taman Sepanjang: Implementasi Pengajaran Karakter Religius Melalui Budaya Sekolah pada Siswa Kelas 3 di Sekolah Dasar Muhammadiyah 2 Taman Sepanjang - Imron, Dita Fathi Chotul; Tirtoni, Feri (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study was to determine the implementation of teaching religious characters through school culture and to describe the supporting and inhibiting factors in the implementation of character teaching through school culture in third grade students of SD Muhammadiyah 2 Taman Sepanjang. This research method uses qualitative with ethnographic approach. Data analysis was carried out using Miles and Huberman's field analysis model. The results showed that the effort to implement the teaching of religious character through school culture was carried out with a habituation program by inviting all school members to work together in building a culture of religious character in the SD Muhammadiyah 2 Taman Sepanjang school environment. Supporting factors in the implementation of teaching religious characters through school culture to students are supporting infrastructure, student enthusiasm, consistency of program implementation and application, norms, school rules and teachers who synergize and coordinate with each other. While the inhibiting factors are the students' willingness, the ability of the teacher to motivate students, limited time, the influence of friends and role models in the home environment.